Odor mixtures: A chord with silent notes - Xu, Lu; Zou, Dong-Jing; Firestein, Stuart (Frontiers in Ecology and Evolution, 2023)
The olfactory world is one of complex mixtures and blends containing up to hundreds of molecules. Many of those molecules can act as agonists, antagonists or enhancers at different receptors. This complicates the mechanism by which higher centers construct perceptions of complex mixtures. We propose that along with structural chemistry, psychophysics, the techniques of medicinal chemistry and machine learning can begin to shed light on this difficult neural problem.